2015
DOI: 10.1177/0091552115571729
|View full text |Cite
|
Sign up to set email alerts
|

The Online STEM Classroom—Who Succeeds? An Exploration of the Impact of Ethnicity, Gender, and Non-traditional Student Characteristics in the Community College Context

Abstract: Objective: This study analyzes how ethnicity, gender, and non-traditional student characteristics relate to differential online versus face-to-face outcomes in science, technology, engineering, and mathematics (STEM) courses at community colleges. Method: This study used a sample of 3,600 students in online and face-to-face courses matched by course, instructor, and semester from a large urban community college in the Northeast. Outcomes were measured using rates of successful course completion (with a "C−" or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 48 publications
(72 reference statements)
9
82
3
Order By: Relevance
“…This finding is in contrast to the findings of Kickmeier‐Rust, Holzinger, Wassertheurer, Hessinger and Albert (), Koh et al () and Mihindo et al (), which showed either better male performance or no gender difference. Our finding also appears to be contrary to the stereotypical view that males may be better at computer technology and females may be better at reading and comprehension (Arellano, ; Lynn & Mikk, ; Shashaani, ; Wladis, Conway, & Hachey, ; Yau & Cheng, ). The significantly higher score growths for female students in WILSIM‐GC group and for test items requiring higher‐level thinking suggest that the visually‐oriented, easy‐to‐use interactive computer simulation approach has helped female students overcome the perceived gender barrier in technology.…”
Section: Interpretation and Discussioncontrasting
confidence: 99%
“…This finding is in contrast to the findings of Kickmeier‐Rust, Holzinger, Wassertheurer, Hessinger and Albert (), Koh et al () and Mihindo et al (), which showed either better male performance or no gender difference. Our finding also appears to be contrary to the stereotypical view that males may be better at computer technology and females may be better at reading and comprehension (Arellano, ; Lynn & Mikk, ; Shashaani, ; Wladis, Conway, & Hachey, ; Yau & Cheng, ). The significantly higher score growths for female students in WILSIM‐GC group and for test items requiring higher‐level thinking suggest that the visually‐oriented, easy‐to‐use interactive computer simulation approach has helped female students overcome the perceived gender barrier in technology.…”
Section: Interpretation and Discussioncontrasting
confidence: 99%
“…However, the year status did not reliably predict retention in a study performed by Traver, Volchok, Bidjerano, and Shea (2014). The mixed results were explained by a possible rationale regarding specific strong traits associated with academic success that were possessed by students regardless of their age (Colorado & Eberle, 2010;Wladis et al, 2015Wladis et al, , 2014. Prediction through genders also yielded mixed results.…”
Section: Demographics Variablesmentioning
confidence: 93%
“…Prediction through genders also yielded mixed results. While women might be worse in online courses in STEM fields (Wladis et al, 2015), there also existed a likelihood of men withdrawing from online courses (Cochran et al, 2014). Therefore, Eliasquevici et al (2017) believed that genders were not necessarily associated with student retention in online learning environments.…”
Section: Demographics Variablesmentioning
confidence: 99%
See 2 more Smart Citations